Correction to "Comments on 'Stability of fuzzy control systems with bounded uncertain delays'". - Xiefu Jang (IEEE Transactions on fuzzy systems)
The research in the above paper (X. Jiang and W. Xu, "Comments on 'Stability of fuzzy control systems with bounded uncertain delays'", IEEE Trans. Fuzzy Syst., vol. 12, pp. 285-286, Apr. 2004) was carried out while the first author was with the Department of Automation, Tsinghua University, Beijing 100084, China. He is now with the Faculty of Informatics and Communication, Central Queensland University, Rockhampton QLD 47012, Australia.